2021
DOI: 10.1007/s10456-021-09773-x
|View full text |Cite
|
Sign up to set email alerts
|

Loss of endothelial glucocorticoid receptor promotes angiogenesis via upregulation of Wnt/β-catenin pathway

Abstract: Objective The glucocorticoid receptor (GR) is a member of the nuclear receptor family that controls key biological processes in the cardiovascular system and has recently been shown to modulate Wnt signaling in endothelial cells. Wnt/β-catenin signaling has been demonstrated to be crucial in the process of angiogenesis. In the current study, we studied whether GR could regulate angiogenesis via the Wnt/β-catenin pathway. Approach and Resultsa Key component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…Notably, many of the GRNs identified by SCENIC featured enriched DNA binding motifs and upregulated gene expression for transcription factors identified in our ATAC-seq and RNA-seq analysis, such as JUN, FOXF1, and LEF1 (Figure 4C). Interestingly, Nuclear Receptor Subfamily 3 group C member 1 (Nr3c1), which encodes a glucocorticoid receptor and is involved in the regulation of WNT/b-catenin pathway (Liu et al, 2021) and albumin D-binding protein (Dbp), a proline amino-acid-rich domain basic leucine zipper (PAR bZip) transcription factor involved in circadian rhythm control in the blood brain barrier (Franken et al, 2000;Pulido et al, 2020), also showed an increase in regulon activity (Supplemental Figure 8A-C).…”
Section: Identification Of Gene Regulatory Network Involved In Brain Endothelial Developmentmentioning
confidence: 99%
“…Notably, many of the GRNs identified by SCENIC featured enriched DNA binding motifs and upregulated gene expression for transcription factors identified in our ATAC-seq and RNA-seq analysis, such as JUN, FOXF1, and LEF1 (Figure 4C). Interestingly, Nuclear Receptor Subfamily 3 group C member 1 (Nr3c1), which encodes a glucocorticoid receptor and is involved in the regulation of WNT/b-catenin pathway (Liu et al, 2021) and albumin D-binding protein (Dbp), a proline amino-acid-rich domain basic leucine zipper (PAR bZip) transcription factor involved in circadian rhythm control in the blood brain barrier (Franken et al, 2000;Pulido et al, 2020), also showed an increase in regulon activity (Supplemental Figure 8A-C).…”
Section: Identification Of Gene Regulatory Network Involved In Brain Endothelial Developmentmentioning
confidence: 99%
“…Our study found that β-catenin pathway was dramatically activated in PF rats, treatment with 3-MA remarkably decreased the expression of β-catenin in fibrotic peritoneum. The activation of autophagy could augment the WNT/β-catenin signaling pathway ( Liu et al, 2021 ), as a result, β-catenin binds to the T cell factor/lymphoid enhancer-binding factor (TCL/LEF) family in the nucleus, and changes the expression of crucial mediators of angiogenesis, such as VEGF ( Liu et al, 2021 ). In addition, autophagy also regulates pigment epithelium derived factor (PEDF) expression, an endogenous VEGF inhibitor, and increases VEGF/PEDF ratio, promoting the formation of neovascularization ( Li et al, 2019b ).…”
Section: Discussionmentioning
confidence: 99%
“… 90 Lack of endothelial the glucocorticoid receptor (GR) triggers autophagy flux, which will lead to activation of Wnt/β‐catenin signalling and promote angiogenesis. 91 In a muscle injury mouse model induced by hindlimb ischaemia, the autophagy pathway was induced under prolonged hypoxia in ECs, which could increase the angiogenic activities of ECs under tissue regeneration and consequently helps regeneration of surrounding tissues. 10 , 91 The transcription factor TFEB, demonstrated as a crucial regulator of lysosomal biogenesis and autophagy, 32 may mediate the link between endothelial autophagy and angiogenesis.…”
Section: Autophagy In Non‐myogenic Cellsmentioning
confidence: 99%
“… 91 In a muscle injury mouse model induced by hindlimb ischaemia, the autophagy pathway was induced under prolonged hypoxia in ECs, which could increase the angiogenic activities of ECs under tissue regeneration and consequently helps regeneration of surrounding tissues. 10 , 91 The transcription factor TFEB, demonstrated as a crucial regulator of lysosomal biogenesis and autophagy, 32 may mediate the link between endothelial autophagy and angiogenesis. Mechanistically, TFEB is up‐regulated in ischaemic skeletal muscle, subsequently activates AMPKα signalling and up‐regulates autophagy, which are essential for angiogenesis during skeletal muscle regeneration.…”
Section: Autophagy In Non‐myogenic Cellsmentioning
confidence: 99%